Effects of Wharton's jelly cells of the human umbilical cord on acute spinal cord injury in rats, and expression of interleukin-1β and nerve growth factor in spinal cord tissues. (3rd July 2016) - Li, Cheng; Chen, Xiao; Qiao, Suchi; Liu, Xinwei; Liu, Chang; Zhu, Degang; Su, Jiacan; Wang, Zhiwei
Abstract : To study the effects of Wharton's jelly cells (WJCs) on acute spinal cord injury (SCI), 81 rats were divided into a sham surgery group, a model group, and a WJC transplantation group ( n = 27). Motor functions of the model and WJC transplantation groups were partially recovered, and the recovery was better in the latter group. The WJC transplantation group had integral spinal cord tissues. Compared with the model group, the WJC transplantation group expressed significantly less interleukin-1β (IL-1β) and more nerve growth factor (NGF) ( P < 0.05). WJC transplantation changed the microenvironment of the SCI site, inhibited IL-1β expression, increased NGF expression, promoted the recovery of neurological function, and relieved secondary SCI.